PERBEDAAN EFEK ANALGESIK AMITRIPTILIN, GABAPENTIN, DAN PREGABALIN PADA NEUROPATI DIABETIK DAN NEURALGIA TRIGEMINAL - Putra, Ibnu; Anwar, Yuneldi; Surbakti, Khairul Putra (PERDOSNI, 2018)
COMPARATIVE ANALGESIC EFFECTS OF AMITRIPTYLINE, GABAPENTIN, AND PREGABALIN IN DIABETIC NEUROPATHY AND TRIGEMINAL NEURALGIAABSTRACTIntroduction: The management of neuropathic pain is a challenge for clinicians because of its nonspecific and difficult clinical to treat characteristics. The e use of antidepressant drugs such as amitriptyline and anticonvulsants such as gabapentin and pregabalin has shown various efficacy overcoming neuropathic pain.Aim: To compare the analgesic Ã‚Â efficacy of amitriptyline, gabapentin, and pregabalin Ã‚Â in patients with diabetic neuropathy and trigeminal neuralgia.Methods: This is an experimental pre and post test study on patients with diabetic neuropathy and trigeminal neuralgia in neurology clinic Haji Adam Malik Hospital, Medan, from April 2015 to march 2017. in each disease, subjects were divided into three groups, each was treated either with oral amitriptyline 12.5mg, gabapentin 100mg, or pregabalin 75mg twice daily. The Numeric Rating Scale to assess pain intensity were examined before and after two weeks after treatment.Results: The number of diabetic neuropathy subjects was 75, while trigeminal neuralgia subjects was 30, each were divided into three groups treated either with amitriptyline, gabapentin, or pregabalin. There were no differences on pain intensity changes in diabetic neuropathy groups but significant differences were shown in trigeminal neuralgia groups.Discussion: Amitriptyline, gabapentin, and pregabalin effective to lower pain intensity in trigeminal neuralgia significantly compare to diabetic neuropathy.Keywords: Amitriptyline, diabetic neuropathy, gabaptentin, pregabalin, trigeminal neuralgiaABSTRAKPendahuluan: Pengelolaan nyeri neuropatik merupakan tantangan bagi klinisi karena karakteristik klinisnya yang nonspesifik dan tatalaksananya yang sulit. Penggunaan antidepresan seperti amitriptilin dan antikonvulsan seperti gabapentin dan pregabalin mempunyai efikasi yang berbeda-beda dalam mengatasi nyeri neuropatik.Tujuan: Mengetahui perbedaan efek analgesik dari amitriptilin, gabapentin, dan pregabalin pada penderita neuropati diabetik dan neuralgia trigeminal.Metode: Studi eksperimental pre dan post test terhadap pasien neuropati diabetik atau neuralgia trigeminal yang berobat ke Poliklinik Neurologi RSUP Haji Adam Malik, Medan, sejak bulan April 2015 hingga Maret 2017. Semua subjek dibagi menjadi tiga kelompok untuk setiap penyakit, yang masing-masing mendapatkan amitriptilin 12,5mg, gabapentin 100mg, dan pregabalin 75mg, dengan frekuensi pemberian obat dua kali sehari setiap kelompok. Pengukuran intensitas nyeri dengan menggunakan Numeric rating Scale dilakukan sebelum dan setelah dua minggu pengobatan.Hasil: Didapatkan subjek dengan neuropati diabetik sebanyak 75 orang dan neuralgia trigeminal 30 orang yang masing-masing dibagi menjadi 3 kelompok dengan terapi amitriptilin, gabapentin, dan pregabalin. Tidak terdapat perbedaan rerata perubahan intensitas nyeri yang bermakna pada kelompok neuropati diabetik, namun bermakna pada subjek neuralgia trigeminal.Diskusi: Amitriptilin, gabapentin, dan pregabalin memiliki efikasi dalam menurunkan intensitas nyeri pada neuralgia trigeminal secara bermakna dibandingkan pada neuropati diabetik.Kata kunci: Amitriptilin, gabapentin, neuralgia trigeminal, neuropati diabetik,pregabalin